Speech perception and hearing outcomes following pediatric bilateral cochlear implants: a scoping review of developmental contextual influences - Corbett, Fleur; Van Zalk, Nejra (Frontiers in Audiology and Otology, 2025)
IntroductionBilateral cochlear implantation is the typical intervention for children with severe-to-profound sensorineural hearing loss, but speech perception and hearing outcomes remain variable. This scoping review explores which contextual factors relate to speech perception and hearing outcomes following pediatric bilateral cochlear implantation based on themes aligned with Bronfenbrenner's bioecological systems theory: (1) individual; (2) microsystem; (3) mesosytem; (4) exosystem; (5) macrosystem; and (6) chronosystem.MethodPRISMA-ScR guidelines were followed to systematically search nine electronic databases with a keyword strategy. Eligible studies were published in English and included an analysis of contextual factors in relation to a behavioral speech perception or hearing outcome measure. Study quality was assessed using Quality Assessment with Diverse Studies (QuADS) criteria and the role of contextual factors in outcomes was explored with a narrative synthesis approach.ResultsTwenty-three research articles met the criteria for inclusion. Contextual factors identified ranged from the proximal to distal context. Contextual factors such as non-verbal cognitive ability, social skills, cochlear implant usage, positive parent-child interactions, educational placement, auditory or oral therapy, ethnicity and prematurity were related to cochlear implant outcomes.DiscussionRelationships between contextual factors and outcomes were not consistent across developmental time or studies. Study quality and methodological limitations are discussed. Research on outcomes related to bilateral cochlear implantation should actively integrate and examine contextual factors in prospective, longitudinal designs. This approach will facilitate the development of interventions to target specific levels of the bioecological system, thereby improving outcomes for the pediatric bilateral cochlear implant recipient.